QUALITY CONTROL OF SANDAL OUTSOLE USING SIX SIGMA METHOD AND FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Nadila Arvianti; Wiwik Sulistiyowati (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: The aim of this research is to determine the type of product defect, determine the production process capability, determine the RPN value, and provide recommendations for improvement. Method: The method used is the Six Sigma method and Failure Mode and Effect FMEA. Results: The research results show that there are 3 types of product defects with a DPMO value of 5109, and a sigma of 4.07. The dominant defect is a rupture defect with a percentage of 70.55%. The main cause of failure is that the engine's heat temperature is unstable. Corrective action that can be taken is to carry out machine maintenance and use a blower in the production area. Novelty: CV. Carita Niaga is a footwear manufacturing company. Sandal outsole is a product that has a lot of demand so it is produced most often and often experiences problems, namely product defects in quite large quantities, namely 1.7%.